A Commentary on "What Grounded Theory Is…": Engaging a Phenomenon from the Perspective of Those Living it. (October 2015) - Corley, Kevin G.
In my editorial and authorial experiences, Grounded Theory approaches to organizational research have proven to be some of the most powerful forms of inquiry we have into modern organizing and organizations. And part of that power comes from its ability to utilize both qualitative and quantitative data. But unlike Walsh et al., I do not believe Grounded Theory is capable of being an all-encompassing research paradigm, nor should it be. The heart and soul of GT methodologies lies in engaging a phenomenon from the perspective of those living it, which means it is most suited toward inductive examinations seeking deep insight into a phenomenon and its connections with the context. Likewise, I also disagree that a GT approach is best used as a sequential, lockstep set of techniques that should be followed precisely; the power of GT approaches is partly derived from the potential to let those closest to the phenomenon influence how it is studied. Yes, I agree that there are key components to the methodology that must be used in combination, but each study is unique (because each phenomenon is unique) and thus there must be room for adaptation and creativity in the implementation of the approach. Ultimately, then, we agree that GT approaches are a powerful way to examine the world around us, but I see much more promise in letting GT bloom and adapt to the phenomena and contexts under study, as opposed to strictly adhering to the original ideas extended by Glaser & Strauss (1967).